Oxidized Alginate-Based Hydrogels for Tissue Engineering Applications: A Review - Reakasame, Supachai; Boccaccini, Aldo R (Biomacromolecules, 2018)
Oxidized alginate (OA)-based hydrogels have drawn considerable attention as biodegradable materials for tissue engineering applications. OA possesses a faster degradation rate and contains more reactive groups compared to native alginate. This review summarizes the research publications reporting the development of OA-based hydrogels for tissue engineering applications including bone, cartilage, blood vessel, cornea, and other soft tissues, highlighting OA key properties and processing approaches.